Non-equilibrium BaxSr1-xSO4 solid solution compositions at elevated Sr2+ concentration, ionic strength, and temperature. (1st November 2022) - Zhao, Yue; Dai, Zhaoyi; Wang, Xin; Dai, Chong; Paudyal, Samridhdi; Ko, Saebom; Li, Wei; Kan, Amy T; Tomson, Mason
Abstract: The Bax Sr1-x SO4 solid solution is ubiquitously present in both geological and industrial processes, where they mostly form under non-equilibrium conditions. Compared with those formed under equilibrium conditions, the Bax Sr1-x SO4 solid solution formed at non-equilibrium condition has significantly higher Sr incorporation at the same aqueous phase compositions. The solid composition of Bax Sr1-x SO4 formed at non-equilibrium condition is critical for the study of chemical palaeoceanography as well as the solid solution nucleation and growth kinetics. However, few studies have been conducted to investigate the composition of the Bax Sr1-x SO4 solid solution when it precipitates at non-equilibrium conditions. In this study, the distribution coefficient of Ba 2+ and Sr 2+ between the Bax Sr1-x SO4 solid solution and the aqueous phases ( K D, Sr-Barite ) at non-equilibrium conditions was studied with barite saturation index ( SI barite ) from 0.9 to 1.5, [Sr 2+ ]/[Ba 2+ ] molality ratio from 0.33 to 30, temperature ( T ) from 50 to 90 °C and ionic strength ( IS ) from 0.01 M to 3 M as NaCl, with celestite being undersaturated. The composition of the Bax Sr1-x SO4 solid solution formed at non-equilibrium conditions can then be calculated from the K D, Sr-Barite values. The results show that the K D, Sr-Barite value decreases with the increase of aqueous Sr 2+ concentration at fixed SI barite and T conditions. The IS effect on the K D, Sr-Barite value is small. Based on the experimental results, a new empirical model is developed to accurately predict the measured compositions of Bax Sr1-x SO4 solid solution at non-equilibrium conditions under a wide T and IS conditions as follows (the plot of the predicted log10 KD, Sr-Barite versus the measured log10 KD, Sr-Barite with R 2 = 0.9995 ) : K D, S r - B a r i t e = - 1.21 - 1.84 SI barite + 1928.1 SI barite × T + a Sr 2 +, a q a Ba 2 +, a q - 1 Several theoretical models have also been compared against the experimental data. The birth and spread crystal growth model (B + S model) could accurately predict the solid composition of Bax Sr1-x SO4 at higher barite SI and/or higher T conditions (barite SI  = 1.5 at 70 °C and barite SI  = 1.2–1.5 at 90 °C with [Sr 2+ ]/[Ba 2+ ] = 0.33–10). However, the B + S model predictions show larger deviations at lower SI and/or lower T conditions (barite SI  = 0.9 and 1.2 at 50 °C and barite SI  = 0.9 at 70 °C with [Sr 2+ ]/[Ba 2+ ] = 0.33–10 in this study). For other theoretical models, such as the CNT model and the BCF model, the predicted solid compositions of Bax Sr1-x SO4 are significantly higher than the measured results. This quantitative study of the Bax Sr1-x SO4 solid solution compositions could help reconstruct oceanic physical conditions and chemistry. It also establishes a solid foundation to further investigate the kinetics of the Bax Sr1-x SO4 solid solution formation during non-equilibrium geological and industrial processes.